Good Things Come in Threes

Geometry Level 4

A B C D ABCD is a square. D F DF is perpendicular to A E AE . If the blue circles are congruent, what is the ratio of the radius of the blue circle to the radius of the red circle? Express the ratio as a + b c \sqrt{\frac{a+\sqrt b}{c} } where b b is square-free. Submit a + b + c a+b+c .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Jan 17, 2021

Extend D C DC and A E AE to meet at G G . Then we note that D F G \triangle DFG and A B E \triangle ABE both have congruent incircles and same three vertex angles. The two triangles are congruent. Therefore D F = E B = x DF=EB=x and let A B C D ABCD be a unit square. We also note that A D F \triangle ADF and A B E \triangle ABE are similar. Therefore,

D F D A = A B A E x 1 = 1 1 + x 2 x 2 = 1 1 + x 2 x 4 + x 2 1 = 0 x = 5 1 2 \begin{aligned} \frac {DF}{DA} & = \frac {AB}{AE} \\ \frac x1 & = \frac 1{\sqrt{1+x^2}} \\ x^2 & = \frac 1{1+x^2} \\ x^4 + x^2 - 1 & = 0 \\ \implies x & = \sqrt{\frac {\sqrt 5-1}2} \end{aligned}

The ratio of the radius of the blue circle to that of the red circle, r b l u e r r e d = A B D F = 1 x = 2 5 1 = 1 + 5 2 = φ \dfrac {r_\blue{\rm blue}}{r_\red{\rm red}} = \dfrac {AB}{DF} = \dfrac 1x = \sqrt{\dfrac 2{\sqrt 5-1}} = \sqrt{\dfrac {1+\sqrt 5}2} = \sqrt \varphi , where φ \varphi denotes the golden ratio . Therefore a + b + c = 1 + 5 + 2 = 8 a+b+c = 1 + 5 + 2 = \boxed 8 .

That's how I did it and I think it's the most elegant solution.

Veselin Dimov - 4 months, 3 weeks ago
Zakir Husain
Jan 17, 2021

Let the square be in a Coordinate plane with origin at point A A and A D , A B \overline{AD}, \overline{AB} lie on y axis and x axis respectively and A B = 1 |\overline{AB}|=1 and let B E = h |\overline{BE}|=h

Let the coordinates of point F F be x 1 , y 1 x_1, y_1

Now, we know that line A B \overline{AB} coincides with line y = h x y=hx and D F \overline{DF} coincide with line y = 1 x h y=1-\dfrac{x}{h} h x 1 = 1 x 1 h \therefore hx_1=1-\dfrac{x_1}{h} x 1 = h h 2 + 1 \Rightarrow x_1=\dfrac{h}{h^2+1} y 1 = h 2 h 2 + 1 \Rightarrow y_1=\dfrac{h^2}{h^2+1} Now, Applying distance formula D F = h 2 ( h 2 + 1 ) 2 + 1 ( h 2 + 1 ) 2 |\overline{DF}|=\sqrt{\dfrac{h^2}{(h^2+1)^2}+\dfrac{1}{(h^2+1)^2}} = 1 h 2 + 1 =\sqrt{\dfrac{1}{h^2+1}} D F = 1 h 2 + 1 |\overline{DF}|=\dfrac{1}{\sqrt{h^2+1}} Similarly, F G = 1 h 1 + h 2 |\overline{FG}|=\dfrac{1}{h\sqrt{1+h^2}} D G = 1 h |\overline{DG}|=\dfrac{1}{h}

Now, let extended D C \overline{DC} and extended A E \overline{AE} intersect each other at point G G with coordinates x 2 , y 2 x_2,y_2

As line A B \overline{AB} coincides with line y = h x y=hx and D C \overline{DC} coincies with line y = 1 y=1 x 2 = 1 h , y 2 = 1 \therefore x_2=\dfrac{1}{h}, y_2=1

Now, as we know that inradius of right triangle with side a , b , c a,b,c where hypotenuse is c = a + b c 2 c=\dfrac{a+b-c}{2}

\therefore inradius of D F G = 1 + h 1 + h 2 2 h 1 + h 2 \triangle DFG = \dfrac{1+h-\sqrt{1+h^2}}{2h\sqrt{1+h^2}}

\therefore inradius of A F E = 1 + h 1 + h 2 2 \triangle AFE=\dfrac{1+h-\sqrt{1+h^2}}{2}

As there inradius are equal according to the question 1 + h 1 + h 2 2 h 1 + h 2 = 1 + h 1 + h 2 2 \therefore\dfrac{1+h-\sqrt{1+h^2}}{\cancel{2}h\sqrt{1+h^2}}=\dfrac{1+h-\sqrt{1+h^2}}{\cancel{2}} 1 + h 1 + h 2 h 1 + h 2 = 1 + h 1 + h 2 \Rightarrow\dfrac{1+h-\sqrt{1+h^2}}{h\sqrt{1+h^2}}=1+h-\sqrt{1+h^2} 1 + h 1 + h 2 = ( h 2 + h ) 1 + h 2 ( h + h 3 ) \Rightarrow 1+h-\sqrt{1+h^2}=(h^2+h)\sqrt{1+h^2}-(h+h^3) ( h 2 + h + 1 ) 1 + h 2 = ( h 3 + 2 h + 1 ) \Rightarrow (h^2+h+1)\sqrt{1+h^2}=(h^3+2h+1) Squaring both the sides ( h 2 + h + 1 ) 2 ( h 2 + 1 ) = ( h 3 + 2 h + 1 ) 2 \Rightarrow (h^2+h+1)^2(h^2+1)=(h^3+2h+1)^2 ( h 4 + h 2 + 1 + 2 h 3 + 2 h 2 + 2 h ) ( h 2 + 1 ) = ( 4 h 2 + h 6 + 1 + 4 h + 4 h 4 + 2 h 3 ) \Rightarrow (h^4+h^2+1+2h^3+2h^2+2h)(h^2+1)=(4h^2+h^6+1+4h+4h^4+2h^3) h 4 + h 2 + 1 + 2 h 3 + 2 h 2 + 2 h + h 6 + h 4 + h 2 + 2 h 5 + 2 h 4 + 2 h 3 = 4 h 2 + h 6 + 1 + 4 h + 4 h 4 + 2 h 3 h^4+\red{\cancel{h^2}}+1+2h^3+\red{\cancel{2h^2}}+2h+h^6+h^4+\red{\cancel{h^2}}+2h^5+2h^4+2h^3=\red{\cancel{4h^2}}+h^6+1+4h+4h^4+2h^3 h 4 + 1 + 2 h 3 + 2 h + h 6 + h 4 + 2 h 5 + 2 h 4 + 2 h 3 = h 6 + 1 + 4 h + 4 h 4 + 2 h 3 \green{\cancel{h^4}}+1+2h^3+2h+h^6+\green{\cancel{h^4}}+2h^5+\green{\cancel{2h^4}}+2h^3=h^6+1+4h+\green{\cancel{4h^4}}+2h^3 1 + 2 h 3 + 2 h + h 6 + 2 h 5 + 2 h 3 = h 6 + 1 + 4 h + 2 h 3 \cancel{1}+\blue{\cancel{2h^3}}+2h+\green{\cancel{h^6}}+2h^5+2h^3=\green{\cancel{h^6}}+\cancel{1}+4h+\blue{\cancel{2h^3}} 2 h + 2 h 5 + 2 h 3 = 4 h \Rightarrow 2h+2h^5+2h^3=4h Dividing both sides by 2 h 2h 1 + h 4 + h 2 = 2 1+h^4+h^2=2 ( h 2 ) 2 + h 2 1 = 0 (h^2)^2+h^2-1=0 From quadratic formula h 2 = 1 + 5 2 h^2=\dfrac{-1{^+_-}\sqrt{5}}{2} as h R h\in\mathbb{R} h 2 = 5 1 2 \therefore h^2=\dfrac{\sqrt{5}-1}{2} h = 5 1 2 h=\sqrt{\dfrac{\sqrt{5}-1}{2}} Now, inradius of A D F = h + 1 1 + h 2 2 1 + h 2 \triangle ADF = \dfrac{h+1-\sqrt{1+h^2}}{2\sqrt{1+h^2}} R a t i o = i n r a d i u s o f D F G i n r a d i u s o f A D F = 1 + h 1 + h 2 2 h 1 + h 2 h + 1 1 + h 2 2 1 + h 2 Ratio=\dfrac{inradius of\triangle DFG}{inradius of \triangle ADF}=\dfrac{\dfrac{\cancel{1+h-\sqrt{1+h^2}}}{\cancel{2}\red{h}\cancel{\sqrt{1+h^2}}}}{\dfrac{\cancel{h+1-\sqrt{1+h^2}}}{\cancel{2\sqrt{1+h^2}}}} = 1 h = 1 5 1 2 =\dfrac{1}{h}=\sqrt{\dfrac{1}{\dfrac{\sqrt{5}-1}{2}}} = 2 5 1 =\sqrt{\dfrac{2}{\sqrt{5}-1}} = 5 + 1 2 =\sqrt{\dfrac{\sqrt{5}+1}{2}} A n s = 5 + 2 + 1 = 8 Ans=5+2+1=\boxed{8}

@Fletcher Mattox how you made the construction image?

Zakir Husain - 4 months ago

Log in to reply

I used GeoGebra

Fletcher Mattox - 4 months ago
Hongqi Wang
Jan 17, 2021

Extend A E AE and D C DC , intersecting at G G : E B A D F G \\ \triangle_{EBA} \sim \triangle_{DFG}

As the blue circles are congruent,so E B A D F G D F = B E E B A A F D A F F D = E B B A = F D A D F D 2 = A F × A D A F 2 + F D 2 = A D 2 A F 2 + A F × A D = A D 2 A F = 5 1 2 A D F D = A F × A D = 5 1 2 A D r b l u e r r e d = B E A F = F D A F = 5 1 2 5 1 2 = 5 + 1 2 a + b + c = 1 + 5 + 2 = 8 \\ \triangle_{EBA} \cong \triangle_{DFG} \implies DF = BE \\ \triangle_{EBA} \sim \triangle_{AFD} \\ \therefore \dfrac {AF}{FD} = \dfrac {EB}{BA} = \dfrac {FD}{AD} \\ \therefore FD^2 = AF \times AD \\ AF^2 + FD^2 = AD^2 \\ AF^2 + AF \times AD = AD^2 \\ \implies AF = \dfrac {\sqrt 5 - 1}{2} AD \\ FD = \sqrt {AF \times AD} = \sqrt {\dfrac {\sqrt 5 - 1}{2}} AD \\ \dfrac {r_{blue}}{r_{red}} = \dfrac {BE}{AF} = \dfrac {FD}{AF} \\ = \dfrac {\sqrt {\dfrac {\sqrt 5 - 1}{2}}}{\dfrac {\sqrt 5 - 1}{2}} = \sqrt {\dfrac {\sqrt 5 + 1}{2}} \\ \implies a+ b + c = 1 + 5 + 2 = \boxed 8

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...